THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY, SERVICE QUALITY AND PROMOTION ON BRAND IMAGE OF TELKOMSEL PRODUCT IN MANADO CITY - Palar, Imanuela Evelyn Angelica; Lapian, Stanss L. H. V. Joyce; Gunawan, Emilia M. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
Brand image is one thing that is very useful for maintaining and increasing business sales. The better the brand image created, customers will glance more at the products or services offered. In the midst of the world of competition that exists between companies, making brand images from a company is important by making efforts to make the brand from the product strong. This study aims to analyse the influence Corporate Social Responsibility, Service Quality, and Promotion on Brand Image of Telkomsel Product on Manado City. The researcher conducted this research through quantitative methods. Multiple Regression Analysis method is used to analyse the influence of the independent variables toward the dependent variable. Sample were taken from the Telkomsel customers in Manado City with a total sample of 100 respondents. The results of this study indicate that Corporate Social Responsibility, Service Quality and Promotion have a positive and significant influence on Brand Image. The results also indicate that Corporate Social Responsibility, Service Quality and Promotion simultaneously influence Brand Image positively and significantly.   Keywords: Corporate Social Responsibility, Service Quality, Promotion, Brand Image